Laparoscopic sleeve gastrectomy versus laparoscopic mini-gastric bypass and early metabolic outcome in super-obese patients - Shaker Nassar, Mohammed Nazeeh; Eldin Abdallah, Abdallah Salah; Anwar Hasan, Hesham Wefky; Mohammed, Ibrahim Aboulfotoh (International Surgery Journal, 2019)
Background: Bariatric surgery became the most popular choice in the management of obesity. Laparoscopic sleeve gastrostomy (LSG) and laparoscopic mini-gastric bypass (LMGB) has taken place in weight-loss and improvement in comorbidities. Methods: This was a retrospective cohort study with equal allocation included 112 super-obese patients with body mass index ≥50 kg/m2, which carried out in General Surgery department of Al-Azhar University Hospitals, between January 2016 and December 2018. 56 patients underwent LSG (Group A), and 56 patients underwent LMGB (Group B). Metabolic effect and weight loss outcomes were evaluated over one year. Results: Operative time was shorter in LSG than LMGB (64.3±33.32 min versus 70±37.24 min). There was a highly significant more weight loss in LSG than in LMGB at 6 and 12 months following the surgery. Also, improvement of type 2 diabetes mellitus, hypertension, hyperlipidemia, and quality of life occurred after 1 year in both surgeries. Conclusions: LSG and LMGB were better optimal procedures for super-obese patients with a comparable percent excess weight loss and improvement of associated comorbidities.